Infrared Thermography for Non-invasive Temperature Monitoring in Smallholder Beef Farm - Nurhidayat Irfan; Suprayogi Agik; Nadia Poetri Okti; Tarigan Ronald (BIO Web of Conferences)
Infrared thermography (IRT) can quickly, easily, and non-invasively measure the quantity of radiation that a thing releases. This study aims to find an alternative to rectal temperature measurement in beef cattle by comparing surface temperatures measured by IRT with rectal temperature under different environmental stress index conditions. Body surface temperatures were measured contactless using IRT at ten different regions, including the forehead, eyes, cheeks, muzzle, ears, neck, legs, costae, flank, and rump. A total of five Simmental-cross (SC) and five Limousin-cross (LC) cows, raised on a local farm in Central Lampung regency, were examined twice a day—once in the morning at 07:00 AM, mild environmental stress index) and once in the afternoon at 12:00 PM, severe environmental stress index). The comparison of rectal and surface temperatures between morning and afternoon showed no statistically significant difference in both SC and LC cows. All body surface temperatures were statistically significantly lower than rectal temperature. Among the body regions studied, the eye region exhibits the strongest correlation with rectal temperature, while showing a very weak correlation with the ambient temperature. We conclude that IRT-measured ocular temperature might be an alternative to rectal temperature in beef cattle.